Extraction of Nickel(II) and Zink(II) by Using A Solvent Impregnated Resin Containing 1-Nitrophenyl-3-methyl-4-octylbenzoyl-5pyrazolone - Ibnu Khaldun; . Rusman; Muhammad Nasir (Syiah Kuala University, 2015)
The study on the equilibrium distribution of nickel(II) and zink(II) between aqueous solution and macromolecular resin impregnated with 1-nitrophenyl3-methyl-4-octylbenzoyl-5-pyrazolone (HNPMOBP, HL) have been conducted. In this research, the effects of pH values, and metal ion concentration on the yield were investigated. Analysis of the results shows that the extraction of the two metal ions can be explained assuming the formation of metal complexes in the resin phase with a general composition ML2. An extraction reaction is proposed and the equilibrium constants of the complexes were determined to be -6.15 and -3.45. The efficiency of the resin in the separation of nickel (II) and zink(II) is provided according to the separation factors. Under the experimental conditions employed, pH50 values for zink (II) and nickel(II) were respectively found to be at 2.76 and 4.95.